Planeación financiera al comercial el palacio del niño de la ciudad de Loja, período 2016 - 2020 - Cartuche Durán, Mónica del Cisne (2016)
The thesis denominated: "FINANCIAL PLANNING TO THE COMMERCIAL THE PALACE OF THE CHILD OF THE CITY OF THE SHOP CITY, PERIOD 2016-2020" was made according to the stipulated to the Regulation of Academic Regime of the National University of Loja, in order to contribute of Effective way that the owner of the commercial can optimize available resources and increase profitability in subsequent periods. The structure of the thesis is aimed at the fulfillment of the objectives outlined at the beginning of our work, as a general objective we have; To carry out a Financial Planning for the Commercial "The Palace of the Child" of the city of Loja, period 2016-2020; Which serves as a guide for an improvement in its fiscal year, as specific objectives, is the elaboration of Forecast Sales and purchases based on sales and purchases of 2015, create a Cash Budget and finally formulate Proforma Financial Statements, which made it possible to forecast The economic-financial situation of the commercial and to know its financial capacity to solve future needs and obligations. The methodology that allowed to fulfill the proposed objectives begins with the collection of reliable information and financial statements provided by the commercial owner, who will lead the development of the Planning by a set of procedures that will allow to obtain future economic results. It was concluded that the company does not carry out a Financial Planning, which does not allow to make adequate decisions on the financial needs that the commercial requires. Therefore it is recommended to apply a Financial Planning that will constitute a tool of great importance when making decisions, prior to making new investments, since basically it is the one that defines the direction of the commercial to reach its objectives.